The Relationship Between HbA1c Levels And Estimated Glomerular Filtration Rate in Prolanis Patients With Type 2 Diabetes Mellitus at Klinik Griya Sehat - Aulisa Siska Nabila; Tasrif Ahmad (Jurnal Biologi Tropis, 2026)
Type 2 diabetes mellitus is a chronic condition that is increasingly prevalent and may result in various complications, including diminished kidney function. The management of blood glucose levels over an extended period in individuals with diabetes can be evaluated through a test for glycosylated hemoglobin (HbA1c), while kidney performance is evaluated by estimating the glomerular filtration rate (GFR). This study aims to determine the relationship between HbA1c levels and estimated glomerular filtration rate in type 2 diabetes mellitus patients enrolled in the Chronic Disease Management Program (Prolanis) at the Griya Sehat Colomadu Clinic. This research is an observational analysis with a cross-sectional approach. The sample included 29 patients with type 2 diabetes mellitus who fulfilled the inclusion criteria. Data on HbA1c levels were gathered from medical files spanning the previous year, while GFR values were determined from serum creatinine levels using the CKD-EPI equation. The analysis of the connection between these two factors was conducted using the Spearman correlation test and the Odds Ratio test. The findings indicated a notable association between HbA1c levels and GFR values, showing a moderate correlation strength (p = 0.012; r = 0.458). The Odds Ratio of 0.370 (95% CI: 0.082-1.667) suggests that individuals with elevated HbA1C levels may have a lower likelihood of experiencing a reduction in GFR; however, this relationship lacks clinical significance. The conclusion drawn is that there exists a significant link between HbA1c levels and the estimated glomerular filtration rate among type 2 diabetes mellitus patients at the Griya Sehat Colomadu Clinic, characterized by a moderate positive association.